Electrode for electrolysis
By using nickel electrodes with a 45-mesh to 60-mesh mesh mesh structure in brine electrolysis and containing ruthenium oxide and nitrogen in the coating, the problems of high overvoltage and poor durability of the cathode are solved, and low overvoltage and high durability are achieved. Electrode performance.
Patent Information
- Application Number
- CN202080045589.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-19
- Filing Date
- 2020-12-14
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-12-14
AI Technical Summary
In the existing salt water electrolysis, the cathode has a high overvoltage and poor durability. Especially when increasing the nickel mesh pore size of the active specific surface area, it is difficult to maintain flatness during the electrode preparation process, and pore clogging is prone to occur.
Using a metal base layer with a mesh structure of 45 mesh to 60 mesh, a single line thickness in the range of 100 μm to 160 μm, and a coating on it contains 20 mole % to 60 mole % of ruthenium oxide and nitrogen by optimizing mesh size and coating components for improved overvoltage and durability.
The electrode performance is achieved with small coating loss, excellent durability, low overvoltage and few hole blockages during the electrolysis process, and the electrolytic efficiency is improved.
Smart Images

Figure BDA0003423675120000101 
Figure BDA0003423675120000111 
Figure BDA0003423675120000121
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to Korean Patent Application No. 10-2019-0170677 filed on December 19, 2019, the disclosure of which is incorporated into this specification by reference. Technical Field
[0004] The present invention relates to an electrolysis electrode capable of improving overvoltage and a method for preparing the electrolysis electrode. Background Art
[0005] The technology of producing hydroxide, hydrogen and chlorine by electrolysis of low-cost brine such as seawater is well known. This electrolysis process is also known as the chlor-alkali process and can be considered a process that has proven its performance and technical reliability in commercial operation for decades.
[0006] For the electrolysis of brine, the most widely used method at present is the ion exchange membrane method, in which an ion exchange membrane is installed in an electrolytic cell to divide the electrolytic cell into a cation chamber and an anion chamber, and brine is used as an electrolyte to obtain chlorine at the anode and hydrogen and caustic soda at the cathode.
[0007] The electrolysis of salt water is carried out by the reaction shown in the following electrochemical reaction formula.
[0008] Anode reaction: 2Cl - →Cl 2 +2e - (E 0 = +1.36V)
[0009] Cathode reaction: 2H 2 O+2e - →2OH - +H 2 (E 0 =-0.83V)
[0010] Overall reaction: 2Cl - +2H 2 O-→2OH - +Cl 2 +H 2 (E 0 =-2.19V)
[0011] In the electrolysis of brine, in addition to the theoretical voltage required for brine electrolysis, the electrolysis voltage must also take into account the overvoltage of the anode, the overvoltage of the cathode, the voltage caused by the resistance of the ion exchange membrane and the voltage caused by the distance between the anode and the cathode, and among these voltages, the overvoltage caused by the electrode is an important variable.
[0012] Therefore, methods capable of reducing overvoltage of electrodes have been studied, wherein, for example, a noble metal-based electrode called DSA (Dimensionally Stable Anode) has been developed and used as an anode, and an excellent material having durability and low overvoltage needs to be developed for a cathode.
[0013] Stainless steel or nickel has been mainly used as the cathode, and, in particular, since the overpotential (η) in the electrolytic reaction is inversely proportional to the active surface area (A), nickel in the form of a woven mesh or an expanded mesh has been mainly used, which can have a large active specific surface area.
[0014] However, when increasing the pore size of the nickel mesh to increase the active specific surface area, it is difficult to ensure flatness during the pretreatment of the substrate during electrode preparation. There is a problem that the mesh pores will be blocked even during the coating formation process. Even when the prepared electrode is used for electrolytic reaction, it will affect the material transfer of the electrolyte and the desorption of hydrogen. Therefore, it is necessary to develop a nickel mesh that meets appropriate conditions.
[0015] Prior art literature
[0016] (Patent Document 1) JP2003-277967A Summary of the invention
[0017] Technical issues
[0018] One aspect of the present invention provides an electrode for electrolysis and a method for preparing the same, in which overvoltage is improved compared with conventional electrodes by optimizing the wire thickness and mesh size of a metal substrate used in the electrode for electrolysis.
[0019] Technical Solution
[0020] According to one aspect of the present invention, there is provided an electrode for electrolysis, comprising: a metal base layer; and a coating layer comprising ruthenium oxide and nitrogen, wherein the metal base layer has a mesh structure with a mesh size of 45 to 60 meshes, a single line thickness of the mesh structure is in the range of 100 μm to 160 μm, and a nitrogen content in the coating layer is in the range of 20 mol % to 60 mol % based on the ruthenium oxide.
[0021] Beneficial Effects
[0022] The electrode for electrolysis of the present invention exhibits excellent durability due to small loss of the coating during electrolysis, and exhibits low overvoltage due to large active specific surface area and less pore clogging caused by the coating. DETAILED DESCRIPTION
[0023] Hereinafter, the present invention will be described in more detail.
[0024] It should be understood that the words or terms used in this specification and claims should not be understood as the meanings defined in common dictionaries. It should also be understood that the words or terms should be understood to have the same meanings as they have in the context of the relevant technology and in the technical concept of the present invention, based on the principle that the inventor can appropriately define the meanings of the words or terms in order to best explain the invention.
[0025] The expression "mesh" as a mesh size unit described in the present invention is defined as the number of meshes included within 1 inch, and, for example, 40 mesh means that the mesh structure has a size of 40 meshes within 1 inch.
[0026] Electrode for electrolysis
[0027] The present invention provides an electrode for electrolysis, comprising: a metal base layer; and a coating containing ruthenium oxide and nitrogen, wherein the metal base layer has a mesh structure with a mesh size of 45 to 60 meshes, a single line thickness of the mesh structure is in the range of 100 μm to 160 μm, and the nitrogen content in the coating is in the range of 20 mol % to 60 mol % based on the ruthenium oxide.
[0028] For conventional electrolytic electrodes, a metal substrate having a mesh size of 40 mesh is mainly used, but in the case of using a 40-mesh mesh structure as the metal substrate of the electrolytic electrode, since a sufficient amount of active specific surface area cannot be provided, there is a problem of relatively high overvoltage. Therefore, the inventors of the present invention have invented an electrolytic electrode having excellent durability due to less detachment of a coating during electrolysis, and at the same time being able to improve overvoltage by optimizing the structure of a metal substrate used in the electrolytic electrode.
[0029] Specifically, the metal substrate of the electrode for electrolysis provided in the present invention has a mesh structure with a mesh size of 45 to 60 meshes, and the thickness of the single wire constituting the mesh structure is in the range of 100 μm to 160 μm. More specifically, the mesh size is in the range of 50 to 60 meshes, and the thickness of the single wire is in the range of 120 μm to 150 μm. In the case where the mesh size of the metal substrate and the thickness of the single wire are respectively within the above range, the detachment of the coating component is small, and the overvoltage is improved. In particular, in the case where the wire thickness is less than the scope of the present invention, the flatness cannot be maintained during the pretreatment process in the electrode preparation process, and scratches will appear even under small impacts due to poor physical durability. In addition, since the effective area is reduced as the wire thickness decreases, the problem of increased overvoltage will occur compared to conventional electrodes. In addition, in the case where the wire thickness is greater than the scope of the present invention, since the single wire is thick, the coating cannot be uniformly formed, the detachment of the coating component will occur more easily, and since a dead volume is generated between the wire and the membrane, a gas trap phenomenon will occur.
[0030] The metal substrate may be nickel, titanium, tantalum, aluminum, hafnium, zirconium, molybdenum, tungsten, stainless steel or an alloy thereof, and, among these metals, the metal substrate may preferably be nickel. In the electrolytic electrode of the present invention, when the above-mentioned type of metal substrate is used, better durability and mechanical strength can be provided to the electrode.
[0031] In the electrode for electrolysis of the present invention, the coating contains ruthenium oxide. Ruthenium oxide plays a role as an active material to provide ruthenium element to the coating, wherein, in the case of using ruthenium oxide in the coating of the electrode for electrolysis, the change of electrode performance over time is small, while the overvoltage phenomenon is improved, and, subsequently, the separate activation process can be minimized. Ruthenium oxide includes all types of oxides in which ruthenium element is bonded to oxygen atoms, and specifically, may be dioxide or tetraoxide.
[0032] In the electrode for electrolysis of the present invention, the coating contains nitrogen. The nitrogen is due to the amine additive contained in the coating composition during the preparation of the coating, wherein, when the amine additive is added to the coating composition, the amine additive can improve the bonding force between the ruthenium elements contained in the coating and the bonding force between the ruthenium element and another metal element when another metal element is contained, and can control the oxidation state of the particles containing the ruthenium element, thereby preparing an electrode in a form more suitable for reaction.
[0033] The nitrogen content in the coating may be in the range of 30 mol% to 70 mol%, for example, in the range of 40 mol% to 60 mol%, based on ruthenium oxide, and, in the case where the nitrogen content is in the above range, the improvement in the bonding force between ruthenium elements can be maximized. In addition, when the nitrogen content is less than the above range, the effect produced by nitrogen is not significant, and, when the nitrogen content is greater than the above range, there is a problem that nitrogen acts as an impurity in the coating instead.
[0034] In the electrode for electrolysis of the present invention, the coating layer may further contain cerium oxide, which plays a role in providing cerium elements to the catalyst layer of the electrode for electrolysis. During activation or electrolysis, the cerium elements provided by the cerium oxide can minimize the loss of ruthenium elements as active materials in the catalyst layer of the electrode for electrolysis by improving the durability of the electrode for electrolysis.
[0035] Specifically, during the activation or electrolysis of the electrolytic electrode, the particles containing the cerium element in the catalyst layer become metal elements that do not change their structure, or are partially hydrated and reduced to active substances. In addition, since the particles containing the cerium element in the catalyst layer change their structure to a needle shape, the particles act as protective materials to prevent the particles containing the ruthenium element in the catalyst layer from physically detaching, and, thereby, the durability of the electrolytic electrode can be improved to prevent the loss of the ruthenium element in the catalyst layer. Cerium oxide includes all types of oxides in which the cerium element is bonded to oxygen atoms, and specifically, may be oxides of (II), (III) or (IV).
[0036] The molar ratio between the ruthenium element and the cerium element contained in the coating layer may be 100:5 to 100:30, for example, in the range of 100:10 to 100:20. When the molar ratio between the ruthenium element and the cerium element contained in the coating layer is within the above range, the balance between the durability and the conductivity of the electrode for electrolysis may be excellent.
[0037] In the electrode for electrolysis of the present invention, the coating may further include platinum oxide. The platinum element provided by the platinum oxide can act as an active material like the ruthenium element, and, in the case where platinum oxide and ruthenium oxide are included together in the coating, better effects can be exhibited in terms of durability and overvoltage of the electrode. Platinum oxide includes all types of oxides in which the platinum element is bonded to oxygen atoms, and specifically, may be dioxide or tetraoxide.
[0038] The molar ratio between the ruthenium element and the platinum element contained in the coating layer may be in the range of 100:2 to 100:20, for example, in the range of 100:5 to 100:15. In the case where the molar ratio between the ruthenium element and the platinum element contained in the coating layer is in the above range, it is desirable in terms of improving durability and overvoltage, wherein in the case where the content of the platinum element is lower than the above range, the durability and overvoltage are reduced, and in the case where the content of the platinum element is higher than the above range, it is disadvantageous in terms of economic efficiency.
[0039] Method for preparing electrode for electrolysis
[0040] The present invention provides a method for preparing an electrode for electrolysis, the method comprising the following steps: applying a coating composition on at least one surface of a metal substrate, the metal substrate having a mesh structure, wherein the mesh size is in the range of 45 mesh to 60 mesh, and the single line thickness of the mesh structure is in the range of 100 μm to 160 μm; and coating the metal substrate coated with the coating composition by drying and heat treating, wherein the coating composition comprises a ruthenium precursor and an amine additive in a molar ratio of 100:5 to 100:20.
[0041] In the method for producing an electrode for electrolysis of the present invention, the metal substrate may be the same as the metal substrate of the electrode for electrolysis described previously.
[0042] In the method for preparing an electrode for electrolysis of the present invention, the coating composition may include a ruthenium precursor and an amine additive. After coating, the ruthenium precursor is converted into an oxide by being oxidized in a heat treatment step.
[0043] The use of the ruthenium precursor is not particularly limited as long as it is a compound capable of forming a ruthenium oxide, and may be, for example, a hydrate, hydroxide, halide or oxide of ruthenium, and may specifically be selected from ruthenium hexafluoride (RuF 6 ), ruthenium(III) chloride (RuCl 3 ), ruthenium(III) chloride hydrate (RuCl 3 ·xH 2 O), ruthenium(III) bromide (RuBr 3 ), ruthenium(III) bromide hydrate (RuBr 3 ·xH 2 O), ruthenium iodide (RuI 3 ) and at least one of ruthenium acetate. When the ruthenium precursors listed above are used, the formation of ruthenium oxide can be easy.
[0044] In the method for preparing an electrode for electrolysis of the present invention, the coating composition may further include an amine additive to provide strong adhesion between the coating and the metal substrate. Specifically, the amine additive may improve the bonding force between the ruthenium elements contained in the coating, and may control the oxidation state of the particles containing the ruthenium element to prepare an electrode in a form more suitable for the reaction.
[0045] The amine additive used in the present invention is particularly suitable for forming a coating because it has high solubility in water while having an amine group. The amine additive that can be used in the present invention includes melamine, ammonia, urea, 1-propylamine, 1-butylamine, 1-pentylamine, 1-heptylamine, 1-octylamine, 1-nonylamine or 1-dodecylamine, and at least one selected from them can be used.
[0046] In the electrode for electrolysis of the present invention, the ruthenium element and the amine additive of the coating may be contained in a molar ratio of 100:20 to 100:40, for example, 100:25 to 100:35. In the case where the amine additive is contained in a range of less than the above molar ratio, the effect of improving the bonding force by the additive is not significant, and in the case where the amine additive is contained in a range of more than the above molar ratio, precipitates are easily generated in the coating liquid, so that not only the uniformity of the coating is reduced, but also the function of the ruthenium oxide is inhibited.
[0047] The coating composition may further include a cerium precursor for forming cerium oxide in the coating layer. The use of the cerium precursor is not particularly limited as long as it is a compound capable of forming cerium oxide, and may be, for example, a hydrate, hydroxide, halide or oxide of the cerium element, and may specifically be selected from cerium (III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O), cerium (IV) sulfate tetrahydrate (Ce(SO 4 ) 2 ·4H 2 O) and cerium(III) chloride heptahydrate (CeCl 3 7H 2 When the cerium precursors listed above are used, the formation of cerium oxide can be easy.
[0048] The coating composition may also include a platinum precursor for forming platinum oxide in the coating. The use of the platinum precursor is not particularly limited as long as it is a compound capable of forming platinum oxide, and, for example, a compound selected from chloroplatinic acid hexahydrate (H2O3) may be used. 2 PtCl 6 6H 2 O), diamine dinitroplatinum (Pt(NH 3 )2 (NO) 2 ), platinum(IV) chloride (PtCl 4 ), platinum(II) chloride (PtCl 2 ), potassium tetrachloroplatinate (K 2 PtCl 4 ) and potassium hexachloroplatinate (K 2 PtCl 6 ). When the platinum precursors listed above are used, the formation of platinum oxide can be easy.
[0049] In the method for preparing an electrode for electrolysis of the present invention, an alcohol solvent may be used as a solvent for the coating composition. In the case of using an alcohol solvent, the above components are easily dissolved, and even in the step of forming a coating layer after applying the coating composition, the adhesion of each component can be maintained. Preferably, at least one of isopropyl alcohol and butoxyethanol may be used as a solvent, and, more preferably, a mixture of isopropyl alcohol and butoxyethanol may be used. Compared with the case of using isopropyl alcohol and butoxyethanol alone, in the case of mixing isopropyl alcohol and butoxyethanol and using them, uniform coating can be performed.
[0050] In the preparation method of the present invention, the preparation method may include a step of pre-treating the metal substrate before coating.
[0051] The pre-treatment may include forming irregularities on the surface of the metal substrate by chemical etching, sandblasting, or thermal spraying.
[0052] The pretreatment may be performed by sandblasting the surface of the metal substrate to form fine irregularities and performing salt or acid treatment. For example, the pretreatment may be performed in the following manner: sandblasting the surface of the metal substrate with aluminum oxide to form irregularities, immersing in a sulfuric acid aqueous solution, washing, and drying to form fine irregularities on the surface of the metal substrate.
[0053] The coating is not particularly limited as long as the catalyst composition can be uniformly coated on the metal substrate and may be performed by a method known in the art.
[0054] The coating may be performed by any one method selected from doctor blade coating, die casting, comma coating, screen printing, spray coating, electrostatic spinning, roller coating and brush coating.
[0055] The drying may be performed at 50° C. to 300° C. for 5 to 60 minutes, and may preferably be performed at 50° C. to 200° C. for 5 to 20 minutes.
[0056] When the above conditions are met, energy consumption can be minimized while the solvent can be sufficiently removed.
[0057] The heat treatment may be performed at 400° C. to 600° C. for 1 hour or less, and may preferably be performed at 450° C. to 550° C. for 5 minutes to 30 minutes.
[0058] When the above conditions are met, it will not affect the strength of the metal substrate while easily removing impurities in the catalyst layer.
[0059] The coating can be performed by sequentially repeating coating, drying and heat treatment so that the coating per unit area (m 2 ) is 10 g or more of ruthenium oxide on the metal substrate. That is, after the catalyst composition is coated on at least one surface of the metal substrate, dried, and heat-treated, the preparation method according to another embodiment of the present invention can be carried out by repeatedly coating, drying, and heat-treating one surface of the metal substrate coated with the first coating composition.
[0060] Hereinafter, the present invention will be described in more detail according to embodiments and experimental examples, but the present invention is not limited to these embodiments and experimental examples. However, the present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. Rather, these exemplary embodiments are provided so that this specification will be thorough and complete, and will fully convey the scope of the present invention to those skilled in the art.
[0061] Material
[0062] In the examples, ruthenium(III) chloride hydrate (RuCl 3 ·nH 2 O) as a ruthenium precursor, platinum (IV) chloride as a platinum precursor, and cerium (III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 In addition, urea was used as an amine additive, and a mixture of 2.375 ml of isopropanol and 2.375 ml of 2-butoxyethanol was used as a solvent for the coating composition.
[0063] Preparation of coating compositions
[0064] 2.41 mmol of ruthenium (III) chloride hydrate, 0.842 mmol of cerium (III) nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O) and 0.1928 mmol of platinum (IV) chloride were fully dissolved in a mixed solvent of the above materials over 1 hour, and 0.045 g of urea was added and mixed to prepare a coating composition.
[0065] Pretreatment of metal substrates
[0066] Before forming a coating on the metal substrate, the surface of the metal substrate used in each of the Examples and Comparative Examples was sandblasted with aluminum oxide (white aluminum oxide, F120) at a pressure of 0.4 MPa, and then the substrate was placed in 5 M H2O2 heated to 80°C. 2 SO 4 The pretreatment was completed by rinsing in an aqueous solution for 3 minutes and then washing with distilled water.
[0067] Example 1
[0068] After pretreatment on a nickel mesh (purity of 99% or more) with a line thickness of 120 μm and a mesh size of 60 meshes by the pretreatment method described above, the pre-prepared coating composition was applied to the pre-treated nickel mesh using a brush. After that, the coated nickel mesh was dried in a convection drying oven at 180° C. for 10 minutes and further heat-treated in an electric heating furnace at 500° C. for 10 minutes. After the above-mentioned coating, drying and heat treatment processes were further performed 9 times, the electrode for electrolysis was finally prepared by heat-treating in an electric heating furnace at 500° C. for 1 hour.
[0069] Example 2
[0070] An electrode for electrolysis was prepared in the same manner as in Example 1 except that a nickel mesh (purity of 99% or more) having a wire thickness of 150 μm and a mesh size of 60 mesh was used as the nickel mesh.
[0071] Example 3
[0072] An electrode for electrolysis was prepared in the same manner as in Example 1 except that a nickel mesh (purity of 99% or more) having a wire thickness of 150 μm and a mesh size of 50 mesh was used as the nickel mesh.
[0073] Comparative Example 1
[0074] An electrode for electrolysis was prepared in the same manner as in Example 1 except that a nickel mesh (purity of 99% or more) having a wire thickness of 150 μm and a mesh size of 40 mesh was used as the nickel mesh.
[0075] Comparative Example 2
[0076] An electrode for electrolysis was prepared in the same manner as in Example 1 except that a nickel mesh (purity of 99% or more) having a wire thickness of 150 μm and a mesh size of 30 mesh was used as the nickel mesh.
[0077] Comparative Example 3
[0078] An electrode for electrolysis was prepared in the same manner as in Example 1 except that a nickel mesh (purity of 99% or more) having a wire thickness of 150 μm and a mesh size of 80 mesh was used as the nickel mesh.
[0079] Comparative Example 4
[0080] An electrode for electrolysis was prepared in the same manner as in Example 1 except that a nickel mesh (purity of 99% or more) having a wire thickness of 180 μm and a mesh size of 60 mesh was used as the nickel mesh.
[0081] Comparative Example 5
[0082] An electrode for electrolysis was prepared in the same manner as in Example 1, except that a nickel mesh (purity of 99% or more) having a wire thickness of less than 80 μm and a mesh size of 60 mesh was used as the nickel mesh.
[0083] Comparative Example 6
[0084] An electrode for electrolysis was prepared in the same manner except that the platinum precursor and urea were not included in the coating composition in Example 1.
[0085] The metal base structure and the ruthenium and nitrogen contents in the coating layers of the electrodes prepared in Examples and Comparative Examples were confirmed by energy dispersive X-ray spectroscopy (EDX) analysis and are summarized in the following Table 1. Bruker D4 Endeavor was used as an instrument for EDX analysis.
[0086] [Table 1]
[0087]
[0088] Comparative Examples 1 to 3 are cases where the mesh size is outside the range of the present invention, Comparative Examples 4 and 5 are cases where the single line thickness is outside the present invention, and Comparative Example 6 is a case where the partial coating component of the present invention is not included. For the Examples, since the coating is smoothly performed, the ratio of nitrogen to ruthenium is higher than that of the Comparative Examples, and, specifically, for Comparative Example 6 in which urea is not included in the coating composition, the nitrogen content is significantly lower than that of the Examples and other Comparative Examples.
[0089] Experimental Example 1. Performance test of prepared electrolytic electrode
[0090] In order to confirm the performance of the electrodes prepared in the examples and comparative examples, performance tests in chlor-alkali electrolysis were performed. A laboratory-scale zero-gap single-cell test device was used as the performance test device, and the cell size was 50 mm×50 mm, wherein an Aciplex F6808 membrane was used. The prepared electrode for electrolysis was used as the cathode, and a commercially available electrode manufactured by AKC was used as the anode. The test conditions included: a current density of 6.2 kA / m 2, a sodium chloride solution with a concentration of 305 g / L was used as the anolyte, a 30.6% NaOH aqueous solution was used as the catholyte, the reaction temperature was 90° C., and the voltage was measured under the above test conditions. The measured voltage values are shown in Table 2 below.
[0091] [Table 2]
[0092]
[0093] According to the above results, for Comparative Examples 1 to 3 whose mesh sizes are outside the scope of the present invention, it can be confirmed that the electrode performance is worse than that of the embodiments of the present invention. In addition, it can be confirmed that the electrode performance of Comparative Example 6, which does not contain nitrogen in the coating component of the present invention, is also worse than that of the embodiments of the present invention. In addition, for Comparative Example 5 whose wire thickness of the mesh structure is less than the scope of the present invention, it can be confirmed that the electrode performance is also worse than that of the embodiments. For Comparative Example 4 whose wire thickness is greater than that of the embodiments, electrode performance similar to that of the embodiments of the present invention is shown.
[0094] Experimental Example 2. Checking for the presence of coating loss before and after the accelerated test
[0095] The presence of coating loss was examined before and after the accelerated test of the electrodes prepared in the Examples and Comparative Examples. The accelerated test was carried out using the prepared electrodes as half cells and at a constant current density (60 kA / m 2 ) for 1 hour, the metal content of the coating before and after the accelerated test was confirmed by an X-ray fluorescence (XRF) analyzer. A 32% sodium hydroxide aqueous solution was used as the electrolyte, a platinum (Pt) wire was used as the counter electrode, and a Hg / HgO electrode was used as the reference electrode. The composition ratios of the ruthenium, cerium and platinum components of the coating before and after the accelerated test are shown in Table 3 below.
[0096] [Table 3]
[0097]
[0098] According to the above results, the coating was hardly detached in the examples of the present invention, but, for Comparative Example 4, which showed an overvoltage similar to that of the present invention, it was found that about 25% of ruthenium loss occurred. The detachment of the coating became a factor that hindered the uniform electrolytic reaction. The change of Ru in Comparative Examples 1 to 3 of more than 100% was confirmed to be due to measurement error.
Claims
1. An electrode for electrolysis, comprising: Metal base layer; and A coating comprising ruthenium oxide and nitrogen, Wherein, the metal base layer has a mesh structure with a mesh size of 50 to 60 meshes, The single line thickness of the mesh structure is in the range of 120 μm to 150 μm, and The nitrogen content in the coating is in the range of 30 mol % to 70 mol % based on the ruthenium oxide, and wherein the coating further comprises platinum oxide, and Wherein, the molar ratio of ruthenium element to platinum element in the coating is in the range of 100:2 to 100:
20.
2. The electrode for electrolysis according to claim 1, wherein The coating also includes cerium oxide.
3. The electrode for electrolysis according to claim 2, wherein: The molar ratio of the ruthenium element to the cerium element in the coating is in the range of 100:5 to 100:
30.
4. A method for preparing the electrode for electrolysis according to any one of claims 1 to 3, the method comprising: applying a coating composition on at least one surface of a metal substrate, the metal substrate having a mesh structure, wherein the mesh size is in the range of 50 mesh to 60 mesh, and the single line thickness of the mesh structure is in the range of 120 μm to 150 μm; and The metal substrate coated with the coating composition is coated by drying and heat treating the metal substrate, The coating composition comprises a ruthenium precursor and an amine additive in a molar ratio of 100:20 to 100:
40.
5. The method according to claim 4, wherein: The amine additive is at least one selected from melamine, ammonia, urea, 1-propylamine, 1-butylamine, 1-pentylamine, 1-heptylamine, 1-octylamine, 1-nonylamine and 1-dodecylamine.
6. The method according to claim 4, wherein: The coating composition also includes a cerium precursor and a platinum precursor.
Citation Information
Patent Citations
Negative electrode, method for producing same, electrolytic cell using same, and hydrogen production method
EP3388553A1
Method for manufacturing hydrogen-manufacturing cathode
JP2003277967A
Electrode for electrolysis and preparation method thereof
US20190211464A1